2022
DOI: 10.3390/su142013355
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Shielding Enhancement of Polyester Adding Artificial Marble Materials and WO3 Nanoparticles

Abstract: The radiation shielding abilities of waste marbles with different concentrations of WO3 (tungsten oxide) nanoparticles were investigated. Four marbles were prepared with 0, 0.05, 0.1, and 0.2 WO3 nanoparticles. The study aims to investigate the effect of the WO3 concentration, the density, and the particle size of the waste marble samples. The linear attenuation coefficient (LAC) of the S1 sample, the sample with no WO3, was determined theoretically and experimentally, and the results demonstrated that they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…At the same time, the nanocomposite could also induce high temperatures under near-infrared irradiation to enhance RT results [97]. A large and growing body of literature [101][102][103][104] has investigated tungsten nanoparticles' radiation protection and shielding effect in medical imaging. Surveys such as that conducted by Wu et al [105] have shown that ultrasmall metal cores and metal-oxide shell nanoparticles, such as CoFe-WO x (CoWO 4 -Fe 2 WO 6 -WO 3 ), can be used as theragnostic nanoprobes for visible/infrared/MRI/CT imaging and photothermal/photodynamic and magnetothermal/magneto-dynamic therapies.…”
Section: Tungsten-based Nanoparticlesmentioning
confidence: 99%
“…At the same time, the nanocomposite could also induce high temperatures under near-infrared irradiation to enhance RT results [97]. A large and growing body of literature [101][102][103][104] has investigated tungsten nanoparticles' radiation protection and shielding effect in medical imaging. Surveys such as that conducted by Wu et al [105] have shown that ultrasmall metal cores and metal-oxide shell nanoparticles, such as CoFe-WO x (CoWO 4 -Fe 2 WO 6 -WO 3 ), can be used as theragnostic nanoprobes for visible/infrared/MRI/CT imaging and photothermal/photodynamic and magnetothermal/magneto-dynamic therapies.…”
Section: Tungsten-based Nanoparticlesmentioning
confidence: 99%
“…Simultaneously high temperature under infrared irradiation is also observed which can enhance the RT efficacy . A considerable amount of work has been done to investigate radiation protection and shielding effect in medical imaging of the tungsten nanoparticles. A survey done by Wu et al presented that ultrasmall metal cores and metal-oxides shell nanoparticles such as CoFe–WOx (CoWO 4 –Fe 2 WO 6 –WO 3 ) can serve as versatile theranostic probes. These probes can be used for visible/infrared/MRI/CT imaging and photothermal/photodynamic and magnetothermal/magnetodynamic therapies .…”
Section: Nanoparticles Used For Theranostic Purposesmentioning
confidence: 99%
“…Pioneering researchers have conducted extensive investigations of the radiation shielding properties of materials produced by combining marble waste with polyester resin. Elhemily, H. and her colleagues [20] investigated the effect of introducing different concentrations and sizes (micro and nano) of tungsten oxide (WO 3 ) on the radiation shielding capabilities of crumbly waste marbles mixed with polyester. Their composites with higher WO 3 concentrations had higher linear attenuation coefficient (LAC) values.…”
Section: Introductionmentioning
confidence: 99%